2011
DOI: 10.4236/health.2011.37070
|View full text |Cite
|
Sign up to set email alerts
|

T cell responses to der f2 mite allergens in Thai allergic patients

Abstract: Dermatophagoides farinae group 2 (Der f2) is a highly polymorphic allergen that shows a distinct pattern of sequence divergence. The effect of the variants on antibody and T cell responses has not been compared. The aim of the present study was to evaluate IgE binding, transcription and translations for IL-5, IFN-γ and TGF-β induced by mite allergens. Sera from 24 HDM-allergic patients and 20 non-allergic subjects were measured for IgE reactivity by ELISA. PBMC was cultured with mite allergens (Df, rDerf2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Most often they are found in habitats intimately associated with humans, such as beds, couches, sofas, other upholstery furnitures, clothing, floors and carpets 4 , 7 , 9 , 10 , 29 . Two mite species D. pteronyssinus and D. farinae are most often found and most abundant in house dust throughout the world 4 , 7 , 9 , 10 , 12 , 14 , 19 , 29 . Laboratory culture studies showed that dust mites do not tolerate relative humidity below 60% (or 55% for D. farinae ) 1 3 , 5 , 12 , 30 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often they are found in habitats intimately associated with humans, such as beds, couches, sofas, other upholstery furnitures, clothing, floors and carpets 4 , 7 , 9 , 10 , 29 . Two mite species D. pteronyssinus and D. farinae are most often found and most abundant in house dust throughout the world 4 , 7 , 9 , 10 , 12 , 14 , 19 , 29 . Laboratory culture studies showed that dust mites do not tolerate relative humidity below 60% (or 55% for D. farinae ) 1 3 , 5 , 12 , 30 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Three species— Dermatophagoides pteronyssinus , Dermatophagoides farinae and Euroglyphus maynei— are reported to be the major allergen sources in house dust 9 , 12 16 . House-dust-mite allergens occurring in an indoor environment are the most important agents of respiratory diseases in humans, including asthma 17 19 .…”
Section: Introductionmentioning
confidence: 99%